PEMANFATAAN EKSTRAK DAUN TANAMAN PULAI (Alstonia scholaris) SEBAGAI HERBISIDA NABATI UNTUK MENEKAN PERTUMBUHAN GULMA RUMPUT TEKI (Cyperus rotundus) - Khairul Anwar; Muhammad Mardhiansyah; Defri Yoza (JURNAL ILMU-ILMU KEHUTANAN, 2020)
Alstonia scholaris contains flavonoids, tannins, triterpenoids, resins and alkaloids. Alkaloid compounds, tannins and flavonoids of plant origin can inhibit weed growth. Alkaloid compounds, tannins and flavonoids work by suppressing the hormone auxin and the hormone gibberelin so that weed growth is inhibited. This study aims to determine the potential of Alstonia scholaris leaves in inhibiting the growth of weed Cyperus rotundus. The inhibition of Cyperus rotundus growth can be seen from changes in leaf color/population phytotoxicity, number of leaves, and height of Cyperus rotundus. The research used Cyperus rotundus leaves which were mashed into flour and then extracted by macerating with alcohol 96% . The results of the extract of Cyperus rotundus leaf flour consisting of a concentration of 0 g/l (control), 25 g/l, 50 g/l, 75 g/l, and 100 g/l were applied to Cyperus rotundus. Pure extracts are given with different concentrations to determine the concentration that is effective in suppressing the growth of Cyperus rotundus. Vegetable herbicides of Cyperus rotundus leaves with a concentration of 50 g/l became the solution to control the enchanted grass weeds that are environmentally friendly without using synthetic herbicides. With the results of phytotoxicity P2= 40.00%, wet weight P2= 1.53 g, and dry weight P2= 0.91 g.